The Effect of Tourism Restriction Policies and Ecology-Oriented Marketing Strategies on Reducing Over-Tourism and Tourist Experience in Indonesia - Gatot Wijayanto; Tera Lesmana; Dila Padila Nurhasanah (Westscience Press, 2024)
This research investigates the effectiveness of tourism restriction policies and ecologically oriented marketing strategies in addressing over-tourism and enhancing tourist experiences in Indonesia. A quantitative analysis was conducted using data collected from tourists visiting selected destinations in Indonesia. The measurement model assessment confirmed the reliability and validity of the constructs, while the structural model analysis revealed significant positive relationships between ecology-oriented marketing strategies and both reducing over-tourism and tourist experience, as well as between tourism restriction policies and these outcome variables. The findings highlight the importance of integrating marketing and policy interventions into destination management practices to achieve sustainable tourism development goals. By adopting a holistic approach, destinations can enhance visitor satisfaction, protect natural and cultural resources, and foster long-term sustainability.